find the sum and simplify
![find the sum and simplify class=](https://us-static.z-dn.net/files/dc2/3a4cc76de6e222cf6191d910ca737760.jpg)
Answer:
[ ( 2 x^2 - x - 5 ) ] / [ ( x + 2 ) ( x - 3 ) ]
option c). is correct.
Step-by-step explanation:
( x + 1 ) / ( x + 2 ) + ( x - 1 ) / ( x - 3 )
= > [ ( x + 1 ) ( x - 3 ) + ( x - 1 ) ( x + 2 ) ] / [ ( x + 2 ) ( x - 3 ) ]
= > [ ( x^2 - 3 x + x - 3 + x^2 + 2 x - x - 2 ) ] / [ ( x + 2 ) ( x - 3 ) ]
= > [ ( 2 x^2 - x - 5 ) ] / [ ( x + 2 ) ( x - 3 ) ]
Hence we get required answer!